Pengaruh Work Life Balance terhadap Kinerja Karyawan - Ranti Lukmiati (Program Studi Manajemen Fakultas Ekonomi UST, 2020)
ABSTRACT This study aims to determine how much influence teh Work Life Balance has on improving the performance of PT. Muara Tunggal production staff, the method used in this study is a quantitative research method with simple linear regression analysis as a data analysis technique, with 46 respondents consisting of 46 using s survey through a quesionnaire to 46 employees of PT. Muara Tunggal, the results of this study can show that Work Life Balance has a positive and significant impact on employee performance. the total effect is 61,6%, the remaining 38,4% is influenced by variables not examined in this study.